Web crippling strength of GI based cold- formed steel under high temperature: experimental and analytical modeling - Sam, Varun Sabu; Anand, N.; Joseph, Deon; Chin, Siew Choo (Springer Science and Business Media Deutschland GmbH, 2025)
Cold-formed steel (CFS) has gained prominence as a structural material for industrial buildings due to its high strengthto-weight ratio and fexibility in design. However, CFS structures are particularly vulnerable to failure under fre exposure, which poses serious safety risks. This study investigates the post-fre web-crippling behavior of galvanized iron (GI) CFS sections under end two fange (ETF) and interior two fange (ITF) loading conditions. Experimental testing was performed on sections without web holes, while parametric analysis explored the impact of 40 and 60 mm diameter web holes. Finite element method (FEM) analysis was used to validate experimental results. Specimens were heated according to the ISO 834 fre curve, followed by cooling through either air or water. A total of 30 specimens—encompassing both ambient and postfre conditions with and without web holes—were analyzed under ETF and ITF loading scenarios. Results demonstrated a signifcant reduction in load-carrying capacity with prolonged heat exposure, with web crippling observed as the predominant failure mode. Unheated sections under ETF loading exhibited a peak load of 12.54 kN, which is notably 66.11% higher than sections heated for 90 min and water-cooled. Additionally, increasing web hole size led to decreases in load capacity, with reductions of 32.61% and 22.74% for 40 mm and 60 mm holes in ETF and ITF conditions, respectively. The fndings underscore the importance of heat exposure duration and cooling methods on the structural performance of CFS sections post-fre.